Place names and landscape in the luso brazilian cartography: 1750-1790 - Fernandes Lima, Eduarda (2023)
The 18th century is marked by the enlightenment scientific renovation and its developments under the iberian empires. This paper focuses on the analysis of sources resulting from ‘viagens filosóficas’ [in english: philosophical voyages] and military expeditions promoted by the Portuguese Crown in the context of the demarcations of the luso-hispanic treaties in the eighteenth century. Such experiences inaugurate new scientific methods and techniques as part of the colonial political projects aimed at harnessing natural wealth and directly controlling territorial domains. This paper aims to understand how the 18th century cartography produced at the time of the demarcation of borders between the Iberian Empires in South America has influenced the construction of new identities based in the geographic space and in the landscape (1750-1790).